(untitled) (European Journal of Interdisciplinary Studies, 2016)
The contemporary phenomenon of migration has already reached global dimensions and differs from the early migrations for the reasons as well as for the course of migration flows. This article aims to provide an overview of the historical evolution that has characterized migration in the European Continent. Passing in different historical stages it explains how Europe as a place of migrant’s departure returns into migration destination. Migration occurs for many different reasons. An analysis of the reasons explains the value that they have been throughout history and how the motives that push entire populations to migrate are the deep needs, fear of war, fear of persecution, torture, till to the desire to improve the social status and the living conditions. And so that migration is not a simply free choice but a necessity. The fact that migration is a constant presence in our society, an ever-evolving phenomenon and that directly affects our societies, have been working impetus to this article.